Genetic Dissection of ICP-Detected Nutrient Accumulation in the Whole Seed of Common Bean (Phaseolus vulgaris L.) - Blair, Matthew Wohlgemuth; Wu, Xingbo; Bhandari, Devendra; Astudillo, Carolina (Frontiers in Plant Science, 2016)
Nutrient transport to grain legume seeds is not well studied and can benefit from modern methods of elemental analysis including spectroscopic techniques. Some cations such as potassium (K) and magnesium (Mg) are needed for plant physiological purposes. Meanwhile, some minerals such as copper (Cu), iron (Fe), molybdenum (Mo) and zinc (Zn) are important micronutrients. Phosphorus (P) is rich in legumes, while sulfur (S) concentration is related to essential amino acids. In this research, the goal was to analyze a genetic mapping population of common bean (Phaseolus vulgaris L.) with inductively coupled plasma (ICP) spectrophotometry to determine concentrations of and to discover quantitative trait loci (QTL) for 15 elements in ground flour of whole seeds. The population was grown in randomized complete block design experiments that had been used before to analyze Fe and Zn. A total of 21 QTL were identified for 9 additional elements, of which four QTL were found for Cu followed by three each for Mg, Mn and P. Fewer QTL were found for K, Na and S. Boron (B) and calcium (Ca) had only one QTL each. The utility of the QTL for breeding adaptation to element deficient soils and association with previously discovered nutritional loci are discussed.